2019
DOI: 10.1016/j.jid.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 1 Deficiency Causes Lethal Skin Blistering

Abstract: effects of caffeine on hair shaft elongation, matrix and outer root sheath keratinocyte proliferation, and transforming growth factor-b2/insulin-like growth factor-1-mediated regulation of the hair cycle in male and female human hair follicles in vitro. Br J Dermatol 2014;171: 1031e43.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Interfering with the superficial DSM cadherin Dsg1 has a similar impact on TJs: in both cases, the TJ protein ZO-1 accumulates aberrantly in the spinous layer, losing its restricted positioning in the SG2 layer (Broussard et al, unpublished data). The importance of Dsg1 for TJs was also observed in Dsg1 knockout animal models 117 (Godsel, Roth-Carter et al, unpublished data). Loss of PKP1, which associates with both DP and Dsg1, also results in impaired TJ function 118 .…”
Section: Desmosomes and Tight Junctionsmentioning
confidence: 69%
“…Interfering with the superficial DSM cadherin Dsg1 has a similar impact on TJs: in both cases, the TJ protein ZO-1 accumulates aberrantly in the spinous layer, losing its restricted positioning in the SG2 layer (Broussard et al, unpublished data). The importance of Dsg1 for TJs was also observed in Dsg1 knockout animal models 117 (Godsel, Roth-Carter et al, unpublished data). Loss of PKP1, which associates with both DP and Dsg1, also results in impaired TJ function 118 .…”
Section: Desmosomes and Tight Junctionsmentioning
confidence: 69%
“…Dsg1 appears to be more critical for epidermal integrity compared to Dsg3 because Dsg3-deficient mice develop mild skin lesions, which spontaneously heal, whereas Dsg1-deficient mice completely lose superficial epidermal layers during birth and die within 24 h (51, 52). However, Dsg3-specific antibodies were effective to cause skin blistering in mice (53) whereas in patients as well as in human epidermis ex vivo antibodies against Dsg3 alone usually are not sufficient to cause skin blisters (1, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Steric hindrance as a mechanism in pemphigus pathophysiology has been suggested by the following evidence: (i) Pathogenic pemphigus Abs recognized the EC1 region that is important for Dsg transinteraction (Ishii et al, 2008;Payne et al, 2005;Sekiguchi et al, 2001), and (ii) Dsg1 and Dsg3 knockout mice showed similar blisters as seen in pemphigus patients (Chen et al, 2008;Koch et al, 1997;Kugelmann et al, 2019). These data suggest that inactivation of Dsgs either by targeting the adhesion domain or genetically eliminating the molecule could result in typical pemphigus lesions.…”
Section: Discussionmentioning
confidence: 94%